Atypical Resting‐State Functional Connectivity of Affective Pain Regions in Chronic Migraine. Issue 5 (1st April 2013) - Schwedt, Todd J.; Schlaggar, Bradley L.; Mar, Soe; Nolan, Tracy; Coalson, Rebecca S.; Nardos, Binyam; Benzinger, Tammie; Larson‐Prior, Linda J.
<x xml:space="preserve">Abstract</x> Objective.— Chronic migraineurs (CM) have painful intolerances to somatosensory, visual, olfactory, and auditory stimuli during and between migraine attacks. These intolerances are suggestive of atypical affective responses to potentially noxious stimuli. We hypothesized that atypical resting‐state functional connectivity (rs‐fc) of affective pain‐processing brain regions may associate with these intolerances. This study compared rs‐fc of affective pain‐processing regions in CM with controls. Methods.— Twelve minutes of resting‐state blood oxygenation level‐dependent data were collected from 20 interictal adult CM and 20 controls. Rs‐fc between 5 affective regions (anterior cingulate cortex, right/left anterior insula, and right/left amygdala) with the rest of the brain was determined. Functional connections consistently differing between CM and controls were identified using summary analyses. Correlations between number of migraine years and the strengths of functional connections that consistently differed between CM and controls were calculated. Results.— Functional connections with affective pain regions that differed in CM and controls included regions in anterior insula, amygdala, pulvinar, mediodorsal thalamus, middle temporal cortex, and periaqueductal gray. There were significant correlations between the number of years with CM and functional connectivity strength between the anterior insula with mediodorsal thalamus and anterior insula with periaqueductal gray. Conclusion.— CM is associated with interictal atypical rs‐fc of affective pain regions with pain‐facilitating and pain‐inhibiting regions that participate in sensory‐discriminative, cognitive, and integrative domains of the pain experience. Atypical rs‐fc with affective pain regions may relate to aberrant affective pain processing and atypical affective responses to painful stimuli characteristic of CM.